Students’ problems in writing the introduction of undergraduate thesis - Cut Mawar Helmanda; Ade M. Novan Novrizal; Siti Safura (ACCENTIA: Journal of English Language and Education, 2022)
The aims of this research were to find the students’ problems, the cause of problems and how students solve the problems in writing thesis in introduction section. Qualitative method was used in this research. The sample of this research was 10 students in English department of Muhammadiyah Aceh University. In collecting data, the researcher applied two instruments, they are: questionnaire and interview. The technique was used to analyzing the data in this research is descriptive analysis. The results of analysis shown that most problems that students faced in writing thesis in the introduction section are: matching the supporting theories, considering the purpose, lack of paraphrase, lack of motivation, lack of grammar, consider the content and organization, and consider the topic. The cause of the problem is their English proficiencies are still low. And the last result of this research is students solved their problem by doing a routine consultation and read lots of sources that related with their thesis.